English Language Teaching and Job-Ready Workforce - Roy, Vijay Kumar (Khwopa Journal, 2025)
There is no balance between the courses offered by higher education institutions and what an institution or organisation demands in job seekers. The imbalance between theoretical knowledge and required skills in a profession is one of the reasons of unemployment. Such imbalance prevents the job seekers to get the jobs of their choice. This paper aims to examine the present status of English language in India in relation to job-ready workforce. It explores the effects of the Covid-19 on job markets and future prospect for the English language learners in India. It also highlights attitudes of the learners towards English, skills-based programmes for the learners, in-service training and professional development programmes offered by educational institutions, and an overall assessment of teaching-learning process in order to prepare job-ready workforce for national and international job markets. The paper also explores the status of the learners and the need of linguistic competency in them and how to prepare them in changing scenario to reduce unemployment in India. Besides the traditional and popular jobs for the graduates in English, some unexplored jobs have been explored in order to enthuse the job seekers to experience new jobs because the youth of today want to work in new environments different from the traditional ones. Mixed method has been used in presentation of the data.